(untitled) (Orfeu, 2021)
This essay proposes a theoretical discussion about music education in times of pandemic, when state-funded and private elementary schools were closed and students were sent contents and tasks to be completed at home. Without a physical, face-to-face space for music lessons, the development of teaching materials faces new challenges. In this scenario, a discussion has taken place on some axes that underpinned the design of teaching materials for elementary education, and (im)possibilities for creative learning were (re)considered as a theoretical foundation and a methodological approach to the accomplishment of creative-musical projects. Finally, a description was made of the principles that can support the creation of educational projects that may help children to express themselves and to engage critically and reflexively in music-making. These practices stimulate their imagination and open up perspectives for connection with music, at home.